Patient reported preferences for sleep interventions among women receiving buprenorphine for opioid use disorder - Eglovitch, Michelle; Parlier-Ahmad, Anna Beth; Legge, Catherine; Chithranjan, Sajanee; Kolli, Saisriya; Violante, Stephanie; Dzierzewski, Joseph M.; Huhn, Andrew Stephen; Wilkerson, Allison; Martin, Caitlin Eileen (Frontiers in Psychiatry, 2023)
Aim Among individuals receiving medication for OUD (MOUD), insomnia is highly prevalent and increases the risk for negative OUD outcomes. However, little is known about MOUD patient-reported preferences for insomnia treatments among women with OUD. This mixed-methods study explored acceptability of and patient preferences for sleep interventions among women in OUD treatment. Methods This is an analysis from an ongoing cross-sectional survey and interview study investigating the relationship between sleep and OUD recovery. The parent study is actively enrolling non-pregnant women between 18–45 years stabilized on buprenorphine from an outpatient program. Participants complete measures including the Insomnia Severity Index (ISI), with scores of ≥10 identifying clinically significant insomnia symptoms. A sub-sample who met this threshold completed semi-structured interviews. Descriptive statistics were generated for survey responses, and applied thematic analysis was used for interview data. Results Participants selected for the qualitative interview (n = 11) highlighted prior positive and negative experiences with sleep treatments, challenges with employing non-pharmacological sleep strategies, and preferences for both medical and behavioral sleep interventions while in recovery. Women emphasized the need for flexibility of sleep therapy sessions to align with ongoing social determinants (e.g., caregiving responsibilities) as well as for sleep medications without sedating effects nor risk of dependency. Conclusions Many women receiving MOUD have concomitant insomnia symptoms, and desire availability of both pharmacologic and behavioral sleep interventions within the OUD treatment setting. Qualitative findings underscore the need for evidence-based sleep interventions that account for the unique socioenvironmental factors that may impact strategy implementation in this population.